Advanced defected ground structures (DGSs) for radio-frequency and millimeter-wave applications - Xu, Shanshan (2017)
The high performance radio-frequency/millimetre-wave filters are highly demanded for modern wireless communication and radar systems. General requirements for high-performance RF filters are low insertion-loss, small form-factor, sharp selectivity, and low manufacturing cost. In the past, substrate integrated waveguide (SIW) has been proven to be effective in integrating planar and non-planar circuits together based on a standard printed circuit board (PCB) to reduce system cost. Inheriting the properties of conventional waveguide, SIW also has good characteristics of low insertion loss, high quality-factor and high power handling capability but with drawback of relative larger circuit size. Meanwhile, defected ground structure (DGS) is an artificial defect on the ground plane. Two unique capabilities of DGS make it a promising solution for filter designs: 1. Prohibiting wave propagation at desired frequencies, namely the stopband property to improve filter selectivity; 2. Slowwave effect for circuit miniaturization applications. This work mainly focuses on the fundamental theory and study of DGS, and its applications to conventional microstrip and SIW filter designs. Several novel DGS structures are proposed and used for high performance miniaturized filter designs. Firstly, a new dual-T DGS is proposed to extend LPF stopband rejection. The DGS is proposed and etched on the ground plane of the transformed radial stub to form a high-performance LPF with wide stopband rejection. Secondly, a new DGS is co-designed with SIR to form a new asynchronously tuned resonator. It is formed by mixed coupled stepped impedance resonator (SIR) and coplanar waveguide SIR (CPW-SIR) is proposed, analyzed, and applied to the 2.4-/5.2-GHz dual-band filter designs. The CPW-SIR is created using DGS on the ground plane. Fractional bandwidth (FBW) design graph is constructed for the dual-band filter synthesis. Two filter prototypes (first-order and fourth-order) are fabricated and measured, which validate our design theory. Thirdly, new DGS structures are developed that form resonators when loaded on SIW technology. A novel back-to-back E-shaped defected ground structure (DGS) for miniaturized dual-band substrate integrated waveguide (SIW) bandpass filter designs is proposed. The SIW loaded by novel DGS supports evanescent-mode wave propagation below the cut-off frequency of SIW, while achieves two transmission poles at the passband and two controllable transmission zero points. Furthermore, the novel loading scheme by loading different-sized DGS resonators on two sides of SIW is proposed for dual-band bandpass filter designs. Meanwhile, the balanced DGSs are investigated for mm-Wave filter applications.